Environmental Generation of Cold Air for Machining - Ginting, Y.; Boswell, B.; Biswas, Wahidul; Islam, M. (2016)
Traditional flood cooling for many companies still remains the preferred method of cooling the cutting zone, even though researchers have shown that using cold air can be a feasible alternative. Providing an energy efficient cooling method needs to be a prime concern for achieving sustainable metal cutting. The objective of this research is to determine the most effective generation of cold air for use during the machining operation. Environmentally-conscious companies are now practically demonstrating that the use of cold air as coolant reduces their disposal costs, and can increase the value of the produced swarf. Technical feasibility of three cold air generating methods will be reviewed, and a sustainability implications of the use of different coolants have been discussed.